Hubungan Antara Motivasi Belajar Dengan Hasil Belajar Geografi Siswa Kelas XI SMA Negeri 1 Kabangka - Wa Ode Asri Safarida; Sitti Kasmiati; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
Based on the results of observations, the motivation of students in class XI IPS1 and IPS2 Senior High School 1 Kabangka is still relatively minimal, where there are still many students who do not care and do not understand the material in Geography subject. The purpose of this research is to find out the relationship between learning motivation and geography learning outcomes for class XI SMA Negeri 1 Kabangka. The sample in this study were 30 people selected using simple random sampling technique. The research instrument was a questionnaire with a Likert scale. The correlation technique used is product moment. The results of the study showed that there was a strong relationship between learning motivation and learning outcomes in geography for class XI students of SMA Negeri 1 Kabangka. The correlation value between the correlation value of variable X and variable Y is 0.84 and the value of "r'' product moment at a significant level of 5% is 2,048, indicating that H0 is rejected and H1 is accepted